2016
DOI: 10.1155/2016/5210865
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble Distillation for Ethanol-Water Separation

Abstract: In the current study, a novel approach for separating ethanol-water mixture by microbubble distillation technology was investigated. Traditional distillation processes require large amounts of energy to raise the liquid to its boiling point to effect removal of volatile components. The concept of microbubble distillation by comparison is to heat the gas phase rather than the liquid phase to achieve separation. The removal of ethanol from the thermally sensitive fermentation broths was taken as a case of study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…The results observed in Figures 4a−c and 5a−d are consistent with an evaporation-condensation switch predicted in previous microbubble evaporation studies. 22,24,25 When a hot microbubble containing completely dry gas comes into contact with an ethanol−water mixture at relatively low temperatures, simultaneous heat and mass transfer occurs and evaporation dominates until the gas is saturated with the volatile components in the mixture. The gas temperature within the bubble continues to drop due to the temperature driving force and condensation starts when the vapor becomes supersaturated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results observed in Figures 4a−c and 5a−d are consistent with an evaporation-condensation switch predicted in previous microbubble evaporation studies. 22,24,25 When a hot microbubble containing completely dry gas comes into contact with an ethanol−water mixture at relatively low temperatures, simultaneous heat and mass transfer occurs and evaporation dominates until the gas is saturated with the volatile components in the mixture. The gas temperature within the bubble continues to drop due to the temperature driving force and condensation starts when the vapor becomes supersaturated.…”
Section: Resultsmentioning
confidence: 99%
“…22−28 Zimmerman et al demonstrated that it is possible to achieve ethanol vapor concentrations higher than the equilibrium values if the contact time between the hot microbubbles and the bulk liquid can be kept to few milliseconds. 24,25 They used microbubbles heated to 90 °C with a liquid height of ∼3 mm to break azeotropic mixtures of ethanol and water kept at 23−25 °C. Numerical simulations of hot microbubbles coming into contact with relatively cold liquids have been performed to understand the dynamics prior to achieving equilibrium conditions, first developed for water evaporation 22 and then later adapted to an ethanol−water system.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a similar factor, demonstration by AlYaqoobi, Hogg, and Zimmerman [7] have found another remarkable difference. They have shown potentially very important qualitative properties of microbubbles in separating ethanol-water mixture -or even azeotropic mixtures not separable by traditional distillation process.…”
Section: Qualitatively Different Properties Of Microbubblesmentioning
confidence: 80%
“…, listed several application of using smaller bubble generated by fluidic oscillator to strip components of liquid such as gas transfer in bioreactors, anaerobic digesters, and particle separation. Various applications of fluidic oscillator generated microbubble have been studied--better oil emulsion separation (Hanotu et al, 2013), higher separation efficiency via microbubble distillation (Al-yaqoobi et al, 2016), better algal growth (Kamaroddin et al, 2016), and efficient yeast recovery (Hanotu et al, 2014).…”
Section: Membrane Fouling and Defoulingmentioning
confidence: 99%